Menyingkap Fakta dan Peristiwa Dibalik Tanda Nabi Yunus - Seri Damarwanti (Sekolah Tinggi Theologia Nazarene Indonesia, 2018)
The books of Old Testament refered to fulfillment the coming of the Messiah in the New Testament. So did the Book of Jonah has written, also the fulfillment of the Messiah in the Gospel. Behind the disagreement in identifying the Book of Jonah as a historical book or parable, an undeniable fact is derived from the words of Jesus Christ, which resulted in the conclusion that